Cultural influences on fidelity components in recovery colleges: a study across 28 countries and territories - Charlotte Hanlon; Lisa Brophy; Peter Bates; Samson Tse; Claire Henderson; Ioannis Bakolis; Mike Slade; Michio Murakami; Julie Cooper; Vicky Stergiopoulos; Michael Ryan; Susana Ochoa; et al. (General Psychiatry)
Background Recovery colleges (RCs) support personal recovery through education, skill development and social support for people with mental health problems, carers and staff. Guided by co-production and adult learning principles, RCs represent a recent mental health innovation. Since the first RC opened in England in 2009, RCs have expanded to 28 countries and territories. However, most RC research has been conducted in Western countries with similar cultural characteristics, limiting understanding of how RCs can be culturally adapted. The 12-item Recovery Colleges Characterisation and Testing (RECOLLECT) Fidelity Measure (RFM) evaluates the operational fidelity of RCs based on 12 components, but cultural influences on these components remain underexplored.Aims To assess associations between Hofstede’s cultural dimensions and RFM items to identify cultural influences on fidelity components.Methods A cross-sectional survey of RC managers was conducted across all 221 RCs. Mixed-effects regression models examined associations between Hofstede’s country-level cultural dimensions and item-level RFM scores, adjusted for healthcare expenditure and income inequality. Four cultural dimensions, obtained from Hofstede, were analysed: individualism (prioritising personal needs), indulgence (enjoyment-oriented), uncertainty avoidance (preference for predictability) and long-term orientation (future-focused).Results The RFM was completed by 169 (76%) RC managers. Seven RFM items showed associations with cultural dimensions. Equality was linked to short-term orientation, while learning was associated with individualism and uncertainty avoidance. Both individualism and indulgence influenced co-production and community focus. Commitment to recovery was shaped by all four cultural dimensions, with the strongest associations seen for individualism and indulgence. Individualism enhanced explicit focus on strengths-based practice, while uncertainty avoidance influenced course distinctiveness.Conclusions This study demonstrates how culture shapes RC fidelity components, providing actionable insights for cultural adaptation. Incorporating under-represented dimensions, such as collectivism and restraint, could improve the RFM’s global applicability, facilitating implementation. Future research should explore cultural nuances, engage diverse stakeholders and refine fidelity measures to enhance RC inclusivity and effectiveness worldwide.